'Healed to imagine': healing discourse in Korean popular culture and its politics. Issue 4 (1st October 2016) - Park, Jin Kyu
Abstract: Healing culture is rapidly growing in the neoliberal late-capitalist context of modern Korea. This study proposes, by defining healing culture as a case of mediated religion, an alternative reading of the culture's contribution to social change, although not disproving altogether the conventional readings that healing culture has ideological, status quo and conforming effects. First, since healing discourse tends to broaden and universalise the subjects of healing into the general society, it reveals that urgent remedies are required for many individuals and, more generally, for the entire society. Second, healing messages initiate a change within the repertoire of the society's accepted discourses, specifically by providing post-materialist values that have been dismissed in the society and by enabling people to imagine an alternative society where post-materialist values are governing.